Analisis Konflik Pilkades Desa Sudimoro Tahun 2020 Terkait Money Politik - Mohammad Fajrul Falah; Agus Machfud Fauzi (Jurnal Pemerintahan dan Politik, 2021)
The election of a village head that becomes a 5-year agenda in a village, apart from being a form of democratic party, is also a new hope and motivation for the village community. The village head election is expected to produce village leader candidates who care for the people so that they can make a major contribution to the progress of the village. Therefore, the enthusiasm of the people to participate in the democratic party performance is expected to be great and the public can channel their voting rights according to their respective consciences. The purpose of this study was to identify and analyze the conflicts that occurred in the Pilkades in Sudimoro village due to the practice of money politics. The research method used in this study is a qualitative method by conducting interviews and observations, then for the theory of researchers using conflict theory from Lewis Coser. The results obtained after research on conflicts that occurred in the Pilkades have become a natural thing as a form of competition to be the best so that they can be chosen by the community.  Keyword: General Election, Village Head, Money Politics, Conflict